INCREASING CORPORATE IMAGE BY THE EMPLOYMENT OF DISABLED PEOPLE - Yaneva, Dilyana; Serafimova, Vesela (Revista Inclusiones, 2020)
Establishing a positive corporate image is a major challenge of modern, dynamic and high technology world. The company's social responsibility is an integral part of this process. The main purpose of this article is to clarify the interrelation between the level of corporate image and the employment of people with disabilities. To achieve the aim of the research a survey has been conducted among 108 Bulgarian companies providing education, finance and accounting services during the period October - December 2019. The research methods used in the article are analysis, synthesis, survey method, graphical methods and summary. The results of the study show that there is a direct correlation between these two processes. The conclusion includes a summary concerning the importance of social corporate policy for building a positive image and competitive advantage of the company.